The role of personality in esl learning - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The main goal of this paper is to discuss how the personality traits extroversion and introversion, as affective factors that condition behavior, can influence the learning of ESL. The investigation focused on the possible correlation between these personality traits and dropout rates in an pre-service teacher education undergraduate course in Brazil. Data collection was carried out by distributing 20 quizzes to students divided into two different groups: 10 students of Portuguese and English as a second language, and 10 students who eventually gave up the second language. Our hypothesis was that the first group would be more extroverted than the second, since most researchers claim that extroverts tend to be better learners. The results proved no correlation between dropout rates and extroversion-introversion personality traits. Both groups were predominantly extroverted in their personal lives but presented characteristics of introverts in the language classes.
Keywords: Letters; Personality; Introversion; Extroversion; Dropout rates; ESL; Letras; Personalidade; Introversão; Extroversão; Evasão; ESL; CNPQ::LINGUISTICA, LETRAS E ARTES